The Philippine Informal Reading Inventory (Phil-IRI) Program: A Critical Analysis - Jennylyn G. Abril; Christian T. Acerbo; Ferdinand T. Abocejo (BIRCU, 2022)
The implementation of the Philippine Informal Reading Inventory (Phil-IRI) program is mandated by the Department of Education (DepEd) for implementation in schools as an assessment tool in determining the performance of learners in reading proficiency. This paper critically analyzed the implementation of Phil-IRI in schools as a prescribed reading program of DepEd. Following a critical analysis approach, the paper explored the problems encountered in the program implementation. The results of the inventory serve as the basis for teachers in creating appropriate reading intervention initiatives to improve the performance of struggling readers. Challenges were revealed along the Phil-IRI implementation which drew setbacks on literacy improvement, writing and reading proficiency of the learners. In the implementation process, some teachers were not adherent nor consistent to program interventions since they are already bombarded with workloads in their teaching tasks and so many paper- works for submission, apart from the time-consuming reading interventions. It was difficult to carry out the appropriate reading remediation in view of teaching time constraints and too many assigned works coupled with the insufficient instructional reading materials, limited or no technological facility and limited library resources. Indeed, developing the reading ability of learners with reading difficulties has never been an easy feat for the reading teachers.